2019
DOI: 10.1186/s12864-019-5873-0
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative proteomic analysis of Tibetan pig spermatozoa at high and low altitudes

Abstract: Background To illuminate the mechanisms underlying the high-altitude tolerance of Tibetan pig spermatozoa, proteomes of spermatozoa from Tibetan pigs raised in high and low altitudes were compared using a tandem mass tag (TMT)-labeled quantitative proteomics approach. Results A total of 77 differentially expressed proteins (DEPs) were identified. Gene Ontology (GO) analysis revealed DEPs that were predominantly associated with the actin cytoskeleton, the tricarboxylic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Tibetan pigs have survived at high altitudes for thousands of years and have adapted to tolerate the hypoxic environment. In our previous studies, we found that although the sperm VAP of Tibetan pigs was signi cantly lower in high-altitude plateau areas compared with low-altitude pigs, their sperm counts, motility and abnormality were equivalent [9]. In the present study, we found that the TP had superior sperm quality compared to the YP on plateaus.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Tibetan pigs have survived at high altitudes for thousands of years and have adapted to tolerate the hypoxic environment. In our previous studies, we found that although the sperm VAP of Tibetan pigs was signi cantly lower in high-altitude plateau areas compared with low-altitude pigs, their sperm counts, motility and abnormality were equivalent [9]. In the present study, we found that the TP had superior sperm quality compared to the YP on plateaus.…”
Section: Discussionsupporting
confidence: 49%
“…Among the 8 candidate proteins, we found that the expression levels of four proteins (FN1, GPX4, VDAC2 and CP) were downregulated in TP spermatozoa, which were enriched in the regulation of the actin cytoskeleton, ferroptosis, and glutathione metabolism ( Table 2). Previous studies have found that bronectin 1 (FN1) is downregulated in spermatozoa of Tibetan pigs living at high versus low altitudes [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tibetan pigs (TP) is a unique and geographically isolated pig breed that inhabits high-altitude regions of the Qinghai-Tibetan Plateau and exhibits heritable adaptations to its hypoxic environment as a result of natural selection [2]. Previously, we determined that the sperm motility of TP in low-altitude and highaltitude areas was 0.84 and 0.82, respectively (no significant difference) [3]. But we have determined that the sperm motility of Yorkshire pigs (YP) that migrated from the lowlands to the plateaus, was 0.80 and 0.73 respectively (a significant decrease).…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [1], the authors reported an error in one of the authors’ names. In this Correction the incorrect and correct author name are shown.…”
mentioning
confidence: 99%